Preparation method of atomic-scale uniformly-mixed homogeneous long-circulation silicon-carbon negative electrode material

By co-depositing and carbon coating of vacuum high-temperature silicon gasified with organic gas, atomic-level uniformly mixed silicon carbon material is formed, which solves the problems of volume expansion, poor conductivity and continuous growth of the surface SEI film of silicon-based anode material, and achieves higher cycle stability and battery capacity.

CN119764372APending Publication Date: 2025-04-04CHANGSHA RES INST OF MINING & METALLURGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411802217.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Silicon-based anode material has problems such as volume expansion, poor conductivity and continuous growth of surface SEI films in lithium-ion batteries, resulting in poor battery capacity attenuation and poor cycle stability.

Method used

Co-deposition of vacuum high-temperature silicon gasified with organic gases is formed to form atomic-level uniformly mixed silicon carbon material, and the outer silicon is coated with carbon to form a protective carbon shell.

Benefits of technology

It effectively alleviates the volume expansion of silicon, improves the conductivity and structural stability of the material, extends the cycle life of the battery, and improves the first-effect performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764372A_ABST
    Figure CN119764372A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lithium ion battery negative electrodes, and discloses a preparation method of an atomic-scale uniformly-mixed homogeneous long-circulation silicon-carbon negative electrode material, which comprises the following steps: gasifying silicon powder at a high temperature in vacuum, co-depositing with organic gas, peeling the deposited material, crushing, sieving, uniformly mixing the crushed material with carbon source powder, and drying to obtain the atomic-scale uniformly-mixed homogeneous long-circulation silicon-carbon negative electrode material. And performing carbonization treatment on the obtained mixture in an inert atmosphere, and performing depolymerization, sieving and demagnetizing on the obtained carbide material, thereby obtaining the product. According to the preparation method, silicon powder is subjected to vacuum gasification to obtain gasified silicon, then the gasified silicon and gasified carbon are subjected to co-deposition, so that silicon and carbon are uniformly mixed on the atomic level, obvious silicon aggregation does not exist, silicon expansion can be effectively relieved, meanwhile, carbon atoms form a conductive network, the problem of poor silicon conductivity is solved, then the surfaces of silicon-carbon co-deposition particles are subjected to carbon coating, and the silicon-carbon co-deposition particles are prepared. The problems of expansion and poor conductivity of exposed silicon particles are solved. And flammable and explosive silane gas is prevented from being used in the preparation process, so that the production process is safe and reliable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium ion battery negative electrodes, and in particular relates to a method for preparing a homogeneous long-cycle silicon-carbon negative electrode material that is uniformly mixed at the atomic level. Background Art

[0002] As the demand for high-energy-density lithium-ion batteries in various fields of battery applications becomes increasingly strong, the capacity of graphite, the mainstream negative electrode of lithium-ion batteries, has reached 360mAh / g, close to the theoretical value of 372mAh / g, and there is very little room for growth. As a representative of new high-capacity negative electrode materials, silicon materials have the advantages of high lithium storage capacity (theoretical specific capacity 4200mAh / g), low lithium desorption potential (<0.5V), and abundant reserves. They are considered to be the most promising next-generation high-energy-density lithium-ion battery negative electrode materials.

[0003] However, there are some application barriers in the large-scale use of silicon-based negative electrode materials: (1) During the charge and discharge process, the insertion and extraction of lithium ions causes a volume expansion of more than 300%, causing the negative electrode material to pulverize and fall off, and eventually causing the negative electrode material to lose electrical contact and completely fail the battery; (2) As a semiconductor, silicon has poor conductivity, which affects its capacity; (3) The continuous growth of the SEI film on the exposed silicon surface will continue to irreversibly consume the limited electrolyte in the battery and the lithium from the positive electrode, eventually leading to a rapid decay of the battery capacity. Therefore, inhibiting the volume expansion of silicon materials, improving their conductivity, and improving the structural stability and surface stability of the materials are of great significance for improving the capacity and cycle stability of silicon materials. Summary of the invention The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a method for preparing a homogeneous long-cycle silicon-carbon negative electrode material with uniform mixing at the atomic level.

[0004] In order to solve the above technical problems, the technical solution proposed by the present invention is: A method for preparing a homogeneous long-cycle silicon-carbon negative electrode material with uniform mixing at the atomic level, comprising the following steps: (1) After silicon powder is gasified under vacuum and high temperature, it is co-deposited with organic gas to obtain a deposited material; (2) peeling the sediment material, crushing and screening it to obtain a crushed material; (3) uniformly mixing the crushed material and the carbon source powder to obtain a mixture; (4) carbonizing the mixture under an inert atmosphere to obtain a carbonized material; (5) The carbonized material is depolymerized, sieved and demagnetized to obtain the homogeneous long-cycle silicon-carbon negative electrode material that is uniformly mixed at the atomic level.

[0005] The present invention aims to co-deposit silicon and carbon by vacuum high-temperature gasification of silicon and high-temperature cracking of an organic gas source, so that silicon and carbon are evenly mixed at the atomic level, and then the exposed silicon on the outer layer is coated with carbon, and finally a silicon-carbon negative electrode material is formed with evenly distributed silicon and carbon inside and an outer layer as a protective carbon shell. Silicon and carbon are evenly distributed at the atomic level, which fully alleviates the expansion of silicon and can effectively improve the cycle performance of the material. At the same time, the evenly distributed carbon atoms can effectively solve the problem of poor conductivity of silicon and improve its capacity. The outer carbon shell can inhibit the formation of SEI film on the surface of the silicon-carbon negative electrode material and improve the initial efficiency and cycle performance of the material. On the one hand, this method avoids the use of flammable, explosive and toxic silane gas, and the production process is safe and reliable; on the other hand, it has fewer processes and can effectively reduce costs.

[0006] In the above preparation method, preferably, in step (1), the particle size of the silicon powder is 3-15 μm.

[0007] Preferably, in step (1), the organic gas is any one of methane, ethane, acetylene and ethylene, or a mixture of several of them.

[0008] Preferably, in the silicon powder and the organic gas, the atomic ratio of silicon to carbon is (45-55): (55-45).

[0009] Preferably, in step (1), the vacuum degree of the vacuum high temperature gasification is -0.9~1.0MPa, the temperature of the vacuum high temperature gas is 1350~1450°C; and the temperature of the co-deposition is 500~800°C.

[0010] Preferably, in step (2), the crushing method is any one or a combination of air flow crushing, grinding crushing, and universal crusher crushing, and the median particle size of the crushed material after crushing and screening is 4-10 μm; preferably 6-8 μm. This particle size range can be more evenly coated on the electrode during the application stage of the material - when the slurry is adjusted to make the electrode.

[0011] Preferably, in step (3), the carbon source is any one of asphalt, resin, lignin, sucrose, and organic acid, or a mixture of several thereof, and the mass ratio of the carbon source powder to the crushed material is (2-20): (98-80).

[0012] Preferably, in step (3), the equipment used for mixing is any one or a combination of a high-speed mixer, a three-dimensional mixer, a plowshare mixer, a high-speed dispersion disk, a ball mill, a double planetary mixer, a mechanical mixer, and a mixing coating machine, the mixing speed is 1000-1500 rpm, and the mixing time is 20-30 min.

[0013] Preferably, in step (4), the carbonization treatment includes a low-temperature carbonization stage and a high-temperature carbonization stage, the low-temperature carbonization temperature is 250-400°C, the high-temperature carbonization temperature is 700-800°C, the heating rate of each stage is 1-10°C / min, the insulation time of each stage is 2-5h, and the whole process is protected by an inert atmosphere. The insulation of the low-temperature stage ensures that the carbon source powder is fully in contact with the crushed material after melting, and the insulation of the high-temperature stage ensures that the carbon source powder is fully carbonized.

[0014] Preferably, in step (5), the median particle size of the sieved long-cycle silicon-carbon negative electrode material is 6 to 12 μm, preferably 7 to 9 μm.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses gas phase silicon and carbon co-deposition to uniformly mix silicon and carbon at the atomic level, without obvious silicon aggregation, which can effectively alleviate the expansion of silicon. At the same time, the carbon atoms therein form a conductive network to solve the problem of poor conductivity of silicon. The surface of the silicon-carbon co-deposited particles is then carbon-coated to solve the expansion and poor conductivity problems of the exposed silicon particles.

[0016] 2. The present invention deposits silicon and carbon simultaneously, has a simple process, and can effectively reduce costs; and avoids the use of flammable and explosive silane to deposit silicon, so the production process is safe and reliable. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 1 is the charge-discharge curve of the silicon-carbon negative electrode prepared in Examples 1 and 2 and Comparative Example 1; Figure 2 is a SEM image of a cross section of the silicon-carbon negative electrode material prepared in Example 1; Figure 3 is a SEM image of a cross section of the silicon-carbon negative electrode material prepared in Comparative Example 1; Figure 4 This is a cross-sectional TEM image of the silicon-carbon negative electrode obtained in Example 1; Figure 5 It is the XRD spectrum of the silicon-carbon negative electrode prepared in Examples 1, 2 and Comparative Example 1. DETAILED DESCRIPTION

[0019] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0020] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0021] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0022] Embodiment 1: A method for preparing a homogeneous long-cycle silicon-carbon negative electrode material with uniform mixing at the atomic level, comprising the following steps: (1) 30g silicon powder was placed in a vacuum sintering chamber with a vacuum degree of -1.0MPa, heated to 1350℃, and acetylene gas was slowly introduced into the high-temperature chamber. The temperature of the high-temperature chamber was 600℃, and the total amount of acetylene gas introduced was 11L. After the deposition was completed, the material obtained from the deposition chamber was peeled, sieved by a universal crusher, and the median particle size of the crushed material was 7μm; (2) adding the crushed material obtained in step (1) and the resin powder into a VCH high-speed mixer and mixing them evenly at a speed of 1500 rpm for 20 min, wherein the mass ratio of the crushed material to the resin is 0.96:0.04; (3) The uniformly mixed material in step (2) is added into a nitrogen-protected tubular furnace for carbonization treatment at a heating rate of 5°C / min. The carbonization temperature is kept at 300°C for 2 h and 750°C for 2 h. After cooling under a nitrogen-protected atmosphere, the material is sieved, depolymerized, sieved and demagnetized to obtain a silicon-carbon negative electrode precursor with a median particle size of 9 μm.

[0023] Embodiment 2: A method for preparing a homogeneous long-cycle silicon-carbon negative electrode material with uniform mixing at the atomic level, comprising the following steps: (1) 30g silicon powder was placed in a vacuum sintering chamber with a vacuum degree of -1.0MPa, heated to 1350°C, and ethylene gas was slowly introduced into the high-temperature chamber. The temperature of the high-temperature chamber was 700°C, and the total amount of ethylene gas introduced was 12L. After the deposition was completed, the material obtained from the deposition chamber was peeled, sieved by a universal crusher, and the median particle size of the crushed material was 6μm; (2) adding the crushed material and asphalt obtained in step (1) into a VCH high-speed mixer and mixing them evenly at a speed of 1000 rpm for 20 min, wherein the mass ratio of crushed material to asphalt is 0.95:0.05; (3) The uniformly mixed material in step (2) is added into a nitrogen-protected tubular furnace for carbonization treatment at a heating rate of 4°C / min. The carbonization temperature is kept at 300°C for 2 h and 700°C for 2 h. After cooling under a nitrogen-protected atmosphere, the material is sieved, depolymerized, sieved and demagnetized to obtain a silicon-carbon negative electrode precursor with a median particle size of 8 μm.

[0024] Comparative Example 1 (Compared to Example 1, it is sand-ground silicon): (1) Add 150g of silicon powder and 850g of isopropanol into a disperser at 500rpm for 30min, stir and disperse evenly to prepare a 15% solid solution, add it into a rod nitrate sand mill at 1250rpm and sand grind for 5h to obtain a silicon slurry with a D50 of 100nm; (2) Add the silicon slurry and liquid resin obtained in step (1) into a double planetary mixer, disperse at 500 rpm, stir at 60 rpm, and mix for 2 hours to obtain a uniformly mixed slurry, wherein the mass ratio of silicon to resin is 55:45; (3) placing the mixed slurry obtained in step (2) in a double cone vacuum drying device, vacuum -0.9 MPa, 120°C, 0.55 rpm, drying for 24 hours, discharging the material, and sieving through a universal crusher; (4) Add the crushed material and asphalt powder obtained in step (3) into a VCH high-speed mixer and mix them evenly at a speed of 8000 rpm for 20 min, wherein the mass ratio of the crushed material to the asphalt powder is 0.92:0.08; (5) The mixed material obtained in step (4) is added to a nitrogen-protected tubular furnace for high-temperature carbonization treatment. The carbonization temperature is 300°C for 2 h and 700°C for 2 h. After cooling under a nitrogen-protected atmosphere, the material is sieved and demagnetized to obtain a silicon-carbon negative electrode precursor.

[0025] The finished materials obtained in Examples 1-2 and Comparative Example 1 were subjected to electrical performance tests by the following method: the finished materials were slurried with a conductive agent and a binder at a mass ratio of 7:2:1, the solid content of the slurry was controlled at 50%, and the slurry was coated on a copper foil current collector to obtain a negative electrode sheet, and the compaction density of the electrode sheet was controlled at 1.6-1.7 g / cm 3 ; Metal lithium sheet was used as the counter electrode, 1mol / L LiPF6 / EC+DMC electrolyte was used to assemble a 2430 button cell. The battery was tested using the LAND battery test system, with a charge and discharge cut-off voltage of 0.005-1.5V. The silicon content and button test results are shown in Table 1, and the charge and discharge curves are shown in Figure 2 shown.

[0026] Table 1: Silicon content and buckling test results of Examples 1, 2 and Comparative Example 1

[0027] It can be seen from Table 1 that, under the condition of equivalent silicon content, compared with the negative electrode material prepared in the comparative example, the material prepared in the embodiment has higher capacity, first efficiency and cycle capacity retention rate, and has obvious advantages in capacity and cycle performance.

[0028] The SEM cross-section of the silicon-carbon negative electrode material prepared in Example 1 and Comparative Example 1 is as follows: Figure 2 , Figure 3 As shown. Figure 2 No agglomerated silicon particles can be observed, and the silicon area and the carbon area cannot be distinguished, indicating that silicon and carbon are uniformly mixed. Figure 3 Obvious strip-shaped silicon particles can be seen in the image, and there is obvious silicon aggregation.

[0029] The silicon-carbon negative electrode obtained in Example 1 was subjected to cross-sectional TEM observation. Figure 4 As shown. Figure 4 It can be seen that silicon and carbon are evenly distributed at the atomic level, and the bright spots are silicon atoms.

[0030] The materials obtained in Examples 1, 2 and Comparative Example 1 were subjected to XRD analysis. The results are as follows: Figure 5 shown. Figure 5 It can be seen that the silicon-carbon negative electrode material obtained in the embodiment is an amorphous material, and the silicon-carbon material obtained in the comparative example has an obvious crystalline silicon diffraction peak, which further illustrates that in the silicon-carbon material obtained in this scheme, silicon and carbon are evenly distributed at the atomic level, and silicon is amorphous silicon.

[0031] In summary, the present invention achieves uniform mixing of silicon and carbon at the atomic level through co-deposition of gas-phase silicon and carbon, without obvious silicon aggregation, which can effectively alleviate the expansion of silicon. At the same time, the carbon atoms therein form a conductive network to solve the problem of poor conductivity of silicon. The surface of the silicon-carbon co-deposited particles is then carbon-coated to solve the problems of expansion and poor conductivity of the exposed silicon particles.

Claims

1. A method for preparing a homogeneous long-cycle silicon-carbon negative electrode material with uniform mixing at the atomic level, characterized in that: The steps include: (1) After silicon powder is gasified under vacuum and high temperature, it is co-deposited with organic gas to obtain a deposited material; (2) peeling the sediment material, crushing and screening it to obtain a crushed material; (3) uniformly mixing the crushed material and the carbon source powder to obtain a mixture; (4) carbonizing the mixture under an inert atmosphere to obtain a carbonized material; (5) The carbonized material is depolymerized, sieved and demagnetized to obtain the homogeneous long-cycle silicon-carbon negative electrode material that is uniformly mixed at the atomic level.

2. The preparation method according to claim 1, characterized in that: In step (1), the particle size of the silicon powder is 3-15 μm.

3. The preparation method according to claim 1, characterized in that: In step (1), the organic gas is any one of methane, ethane, acetylene and ethylene, or a mixture of several of them.

4. The preparation method according to claim 1, characterized in that: In step (1), in the silicon powder and the organic gas, the atomic ratio of silicon to carbon is (45-55): (55-45).

5. The preparation method according to claim 1, characterized in that: In step (1), the vacuum degree of the vacuum high temperature gasification is -0.9~1.0MPa, the temperature of the vacuum high temperature gas is 1350~1450°C; and the temperature of the co-deposition is 500~800°C.

6. The preparation method according to claim 1, characterized in that: In step (2), the median particle size of the crushed material after crushing and screening is 4-10 μm.

7. The preparation method according to claim 1, characterized in that: In step (3), the carbon source is any one of asphalt, resin, lignin, sucrose, and organic acid, or a mixture of several of them, and the mass ratio of the carbon source powder to the crushed material is (2-20): (98-80).

8. The preparation method according to claim 1, characterized in that: In step (3), the mixing speed is 1000-1500 rpm and the mixing time is 20-30 min.

9. The preparation method according to claim 1, characterized in that: In step (4), the carbonization treatment includes a low-temperature carbonization stage and a high-temperature carbonization stage. The carbonization temperature in the low-temperature stage is 250-400°C, and the carbonization temperature in the high-temperature stage is 700-800°C. The heating rate of each stage is 1-10°C / min, and the insulation time of each stage is 2-5h. The whole process is protected by an inert atmosphere.

10. The preparation method according to any one of claims 1 to 9, characterized in that: In step (5), the median particle size of the sieved long-cycle silicon-carbon negative electrode material is 6 to 12 μm.